Loading of cell cultures with cholesterol-dextran particles as a new functional test for Niemann-Pick type C disease - Majer, Filip; Asfaw, Befekadu; Kuchař, Ladislav; Mušálková, Dita; Steiner-Mrázová, Lenka; Dobrovolný, Robert; Ledvinová, Jana; Hřebíček, Martin (Journal of inherited metabolic disease, 2022)
Deuterium-labeled cholesterol-dextran particles (d4-CholDex), prepared by co-precipitation, were internalized by cultured human skin fibroblasts and HEK293 cells. Subcellular particles from d4-CholDex-treated HEK293 cells were fractionated on iodixanol gradients. More than 60% of d4-cholesterol (d4-UC) in the gradient co-fractionated with lysosomal markers and NPC1. This and formation of d4-cholesteryl esters (d4-CE) in the cells suggests that d4-CholDex is lysosomally processed. In accordance with these findings, we observed an increase in lysosomal cholesterol content by fluorescence microscopy in CholDex-loaded cells. Fibroblast cultures including 13 NPC1-deficient, four heterozygous and six control lines were treated with d4-CholDex at final d4-UC concentration of 0.05 mg/ml (127.98 μmol/L) for 3 h and chased for 48 h in medium without d4-CholDex. Concentrations of d4-UC and d4-CE in harvested cells were measured by tandem mass spectrometry (MS/MS). d4-UC/d4-CE ratios were elevated in NP-C lines compared to controls (n = 6, mean = 4.36, range = 1.89-8.91), with the highest ratios in severe NP-C1 phenotypes and the lowest in adolescent/adult type patients. There were overlaps between NP-C1 forms: early infantile (n = 1, mean = 48.6), late infantile (n = 4, mean = 36.3, range = 20.6-54.0), juvenile (n = 5, mean = 24.7, range = 13.4-38.3), adolescent/adult (n = 3, mean = 14.5, range = 11.7-19.8). The ratios in NP-C1 heterozygotes were mildly elevated (n = 4, mean = 16.4, range = 14.9-17.4) and comparable to patients with adolescent/adult NP-C1. The test can be useful in evaluation of suspected NP-C patients with inconclusive results of biomarker or molecular tests. Its advantages include standardized preparation of particles with longer shelf life at 4 °C, quantitative results, and no requirement for radioactive chemicals.
Keywords: HEK293 Cells; HEK293 buňky; Adolescent; Cholesterol; Niemann-Pick Disease, Type C; buněčné kultury; cholesterol; lidé; protein NPC1; Cell Culture Techniques; tandemová hmotnostní spektrometrie; Niemann-Pick C1 Protein; Dextrans; mladiství; Niemannova-Pickova nemoc typu C; dextrany; Tandem Mass Spectrometry; Humans